Two-year effects of the community-based overweight and obesity intervention program Gezond Onderweg! (GO!) in children and adolescents living in a low socioeconomic status and multi-ethnic district on Body Mass Index-Standard Deviation Score and quality of life. (December 2021) - Lek, Dagna; Haveman-Nies, Annemien; Bezem, Janine; Zainalabedin, Sonay; Schetters-Mouwen, Safina; Saat, Jenneke; Gort, Gerrit; Roovers, Lian; van Setten, Petra
ABSTRACT: Background: In most childhood obesity interventions, disadvantaged groups are underrepresented, and results are modest and not maintained. A long-term collaborative community-based approach is necessary to reach out to children from multi-ethnic backgrounds and achieve sustainable behavior change, resulting in sustained Body Mass Index-Standard Deviation Score (BMI-SDS) reductions. The objective is to determine the effects of GO! on BMI-SDS and Health-Related Quality of Life (HRQoL) for children and adolescents having overweight or obesity. Methods: A prospective, longitudinal cohort study was used to collect two-year follow-up data from November 2014 to July 2019. Children and adolescents (4-19 years old) from the low socioeconomic status and multi-ethnic district of Malburgen in the Dutch city of Arnhem were included. 178 children having overweight or obesity were recruited, with 155 children measured at baseline and after two years as a minimum, while 23 were lost to follow up. Participants attending the program for over six months were defined as completers (n=107) and participants attending the program for less than six months were defined as non-completers (n=48). The child health coach (CHC) acts as a central care provider in the collaborative community with healthcare providers from both medical and social fields. This coach coordinates, monitors and coaches healthy lifestyles, while increasing self-management for both children and parents. This is done in a customized and neighborhood-oriented manner and provided by all the stakeholders involved in GO!. The main outcomes are the change in BMI-SDS scores and HRQoL scores reported by participants. Findings: After 24 months, completers showed a decrease in BMI-SDS of -0·32 [95% CI: -0·42, -0·21], compared with -0·14 [95% CI: -0·29, 0·01] for non-completers (adjusted for gender and ethnicity; P=0.036). While 25% suffered from overweight and 75% from obesity at the start, following the intervention 5% showed normal weight, with 33% overweight and 62% with obesity. HRQoL reported by participants improved over time, showing no differences between completers and non-completers, gender and ethnicity after two years. Interpretation: Our results suggest that the GO! program might be effective in reaching out and reducing BMI-SDS for participants in a low socioeconomic status and multi-ethnic district over a two-year period. We noticed also trends to beneficial shifts in obesity grades. HRQoL improved regardless of the participation rate, gender and ethnic background. In light of the study limitations, further studies are needed to corroborate our observations. Funding: Dullerts-foundation, Nicolai Broederschap foundation, Burger en Nieuwe weeshuis foundation, Rijnkind foundation, Arnhems Achterstandswijken foundation,  Menzis-foundation, the municipalities of Arnhem, Rheden, Overbetuwe and Lingewaard, the Association of Dutch municipalities, and Province of Gelderland.